MIXED PAIN PADA LOW BACK PAIN: ELABORASI DAN IDENTIFIKASI - Juwita; Dessy R. Emril; Rachmad Suhanda (Neurologi Manado, 2022)
Low back pain is a health problem that is very common and has an impact on the financial well-being of both patients and their families. Based on pathophysiology, pain can be divided into nociceptive, neuropathic, and central sensitization pain. In about 85% low back pain cases, it is not known which type of pain plays a greater role so that patients suffer from pain for more than 1 year. Currently known as Mixed Pain, namely pain with a combination of pathophysiology that underlies the pain such as nociceptive with neuropathic pain. The term pain cannot yet be formally defined, so the term mixed pain has not been used widely enough to define pain. It is necessary to conduct a search on clinical indicators of mixed pain so that the process of identifying the type of pain is better, the selection of therapy becomes more rational, and the patient's quality of life improves.